(untitled) (REMUNOM, 2024)
Abstract The purpose of this article was to analyze the (in)applicability of custody, visitation and food for domestic animals in the event of divorce from their guardians, in light of current Brazilian legislation. The main objective is to address the fate of pets after the breakup of the marital bond. Animals are considered family members, actively participating in the family nucleus, thus constituting a multispecies family, which is based on the affection inherent in the human-animal relationship. In addition, they were recognized as sentient beings, who have the capacity to feel a variety of emotions. With the paradigm shift, several lawsuits arose to be considered by the Judiciary, involving requests for custody, visitation and food for pets after divorcement. Given this conflict and the gap in Brazilian legislation, the lawsuit needs to receive judicial protection. Therefore, based on case law and doctrine, it is possible to plead such claims before the Judiciary and the institutes of Family Law are applicable in a similar way to domestic animals, with the judging body being responsible for adapting to the specific case. Through bibliographic research method, analysis of judgments and civil law doctrine, it was possible to answer this question.